2007
DOI: 10.1089/apc.2006.0165
|View full text |Cite
|
Sign up to set email alerts
|

Global Cardiovascular Risk in Patients with HIV Infection: Concordance and Differences in Estimates According to Three Risk Equations (Framingham, SCORE, and PROCAM)

Abstract: To compare cardiovascular risk stratification according to Framingham, PROCAM (Prospective Cardiovascular Münster), and SCORE (Systematic Coronary Risk Evaluation) equations in patients with HIV infection, a cross-sectional study of a well-characterized cohort of 760 HIV-infected adults managed at the outpatient Infectious Disease Unit in 2003 was conducted. Cardiovascular risk score was examined and patients were classified as having low, moderate, or high risk using Framingham and PROCAM (<10%, 10%-20%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 24 publications
9
42
2
6
Order By: Relevance
“…Because there is still controversy regarding the application of these population-derived CVD risk scores to HIVinfected patients [12][13][14][15], we decided to assess the agreement of the FRS with the presence of subclinical atherosclerosis in a representative sample of this HIVinfected patient population. We found a good concordance between the estimated FRS and atherosclerosis (as measured by CIMT) in patients with FRS 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there is still controversy regarding the application of these population-derived CVD risk scores to HIVinfected patients [12][13][14][15], we decided to assess the agreement of the FRS with the presence of subclinical atherosclerosis in a representative sample of this HIVinfected patient population. We found a good concordance between the estimated FRS and atherosclerosis (as measured by CIMT) in patients with FRS 10%.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up of patients within the D:A:D study reported that HIV-infected patients receiving antiretroviral treatment had a risk of developing myocardial infarction that was similar to, or somewhat higher than, that predicted by the FRS [11]. In addition, more recent reports suggest that FRS may underestimate the real CVD risk in HIV-infected patients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Increased immune activation of monocytes was reported to be involved in HIV-1 pathogenesis and thus associated with CVD risk. 17,28,29 In the present study, we demonstrated that in contrast to the decreased percentage of CD14 high CD16 2 monocyte subset, CD14 dim CD16 1 and CD14 high CD16 1 monocyte subsets were expanded during both primary and chronic HIV-1 infection.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectionmentioning
confidence: 99%
“…18 MPA is regarded as a more sensitive marker of platelet activation than P-selectin (CD62P), a molecule that binds to Pselectin glycoprotein ligand-1 (PSGL-1) on monocytes, and is closely correlated with thromboembolic events. [19][20][21] Cardiovascular risks are increased in HIV-1-infected patients, [22][23][24] and this increase may be due to a mechanism involving monocyte subset distribution, activation, and MPA formation disorders. Increased MPA formation was previously reported in HIV-1-infected patients receiving antiretroviral therapy and in simian immunodeficiency virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study of HIV-1 infected patients in a Spanish outpatient setting demonstrated that the traditionally used Framingham risk calculation score identified a higher proportion of HIV-1 infected men with a moderate cardiovascular risk compared to other available risk stratification tools (Knobel et al, 2007). However, this tool may not be equally applicable to all populations -for example, in a study which examined the predicted cardiovascular risk in an HIV-1 infected Thai population, the Framingham calculation over estimated the risk of cardiovascular disease compared to other cardiovascular risk equations (Edwards-Jackson et al, 2011).…”
Section: Assessment and Management Of Patients With Increased Cardiovmentioning
confidence: 99%